MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN CORE (CONNECTING, ORGANIZING, REFLECTING & EXTENDING) BERBANTUAN MIND MAPPING PADA MATERI HIDROLISIS GARAM - Muhammad Fahmi Rijal; Rusmansyah Rusmansyah (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2016)
Abstract: Has done research on the use of CORE (Connecting, Organizing, Reflecting & Extending) learning model assisted mind mapping on the material salt hydrolysis student of class XI MIA 3 SMAN 6 Banjarmasin which aims to determine (1) the activities of teachers; (2) the activites of students; (3) improving student learning outcomes; and (4) the response of students to learning. The research design was used classroom action research with 2 cycles with completely four meeting. Each cycle consists 4 stages of planning, action, observation and evaluation, as well as analysis and reflection. The subjects were 38 students of class XI MIA 3 SMAN 6 Banjarmasin. Data were collected through observation, and achievement test. Data The results showed that: (1) an increase in activity of the teachers in the first cycle is 3,37 with category good enough to 4,20 with category good in the second cycle; (2) an increase in activity of students from average in the first cycle is 3,38 with category active enough, in the second cycle to 4,20 with category active; (3) an increase in students cognitive aspec from 65,09 with predicate less and The percentage of students that have pas is 63,16% in the first cycle to 79,65 with predicate medium and teh percentage of students that have pass is 81,58% in the second cycle. Outcomes of students affective increase from the average in the first cycle is 2,52 with category good enough to 14,97 in the second cycle with category good. Outcomes of students skill increase from average in the first cycle is 67,95 with predicate less competent to 83,7 with predicate competent in the second cycle and (4) students class XI MIA 3 of SMAN 6 Banjarmasin give the best responsibility to learning by using CORE learning model assisted mind mapping on the material salt hydrolysisKeywords: CORE learning model, mind mapping, learning outcomes